The Status and Impact of Bio Safety Regulation in Developing Economies Since Ratification of the Cartagena Protocol - McLean, Morven (World Bank, Washington, DC, 2014)
The World development report 2010: development and climate change highlights the link between biotechnology, development, and environment. Aside from recognizing biotechnology's potential to improve crop productivity, increase crop adaptation to climatic stresses such as drought, and mitigate greenhouse gas emissions, the report emphasizes the need to establish science-based regulatory systems 'so that risks and benefits can be evaluated on a case-by-case basis, comparing the potential risks with alternative technologies' (World Bank 2010). This paper explores how the Cartagena protocol to the convention on biological diversity, as well as other important drivers, have affected the regulation of Genetically engineered (GE) crops in developing countries. It examines the impact of biosafety regulation on research and development of GE crops and on product approvals. Finally, it identifies opportunities to advance biosafety regulation in those developing countries that wish to access the potential benefits of agricultural biotechnology. As is true for capacity development in other regulatory arenas, progress in biosafety regulation in developing countries is often impeded by limited political and financial commitments from national governments and by insufficient technical, human resource, and institutional capacity for implementation. It is also confounded by competing or redundant capacity building projects and the absence of products to regulate.